Mechanism of biological control of root rot of groundnut caused by Macrophomina phaseolina using Pseudomonas fluorescens - MEKALA CHARITHA DEVI*, BASAVARAJU SREEDEVI and (Indian Phytopathology, 2012)
Pseudomonas fluorescens isolated from groundnut rhizosphere soil were evaluated for their antagonistic activity against M. phaseolina. P. fluorescens isolate, Pf3 was high siderophore producer and plant growth promoter. This isolate also inhibited the mycelial growth of M.phaseolina and decreased the root rot incidence under green house conditions. Biochemical changes in P. fluorescens Pf3 treated plants, M. phaseolina inoculated plants and healthy plants were assayed at different stages of infection. The efficacy of P. fluorescens Pf3 isolate was tested for the induction of systemic resistance against M. phaseolina. Total phenols, ortho-dihydric phenols, peroxidase and polyphenol oxidase activities increased at different stages of infection.